A Zero Waste In Micro, Small And Medium Enterprises As A Model Of Increasing Income In The Framework Of Sustainable Business - Hanifah, Risti Ulfi; Safitri, Candra -; Budiartono, Agung - (Journal of Economic Education, 2023)
The take-make-waste model is the dominant model of linear economic growth, assuming that natural resources are widely and unlimitedly available since their reconception during the industrial revolution. The environment is something that is very close to life based on the interaction of nature with society, even has a very wide scope as it develops. Zero waste is a philosophy that is used as a lifestyle to encourage the life cycle of resources, so that existing products can be reused more optimally. In order to prevent the use of materials that are difficult to decompose and overcome the large amount of waste left over from business, MSMEs can apply the concept of zero waste in increasing income. Very minimal education and unorganized management are one of the factors for the lack of awareness to apply a zero waste lifestyle in everyday life and sustainable business. The purpose of this study is to reveal the meaning of the zero waste approach to MSMEs as a model of increasing income in business sustainability. The research used is based on qualitative descriptive by collecting data, interviews, documenting the results of zero waste in the community, and looking at the potential for increasing MSME income. The results showed that the implementation of zero waste carried out by MSMEs can increase income. Waste in the form of patchwork can be reprocessed into handicrafts in the form of cellphone hangers, women's clothing in the form of dresses and wall crafts carried out by MSMEs Batik Laksmi Art Kampoeng Djaodhoel to produce use value. The proceeds from the sale of processed waste can increase the income of MSMEs actors. In addition, the level of awareness in MSME actors towards the environment is very high. Factors such as the potential for zero waste-based community waste treatment that can be applied by the surrounding community in a sustainable manner and the potential for providing a forum for economic activity in Kampoeng Djadhoel MSME activities.